Peran Guru dalam Pembelajaran Praktik Shalat Melalui Pembiasaan Anak Usia Dini di PAUD Perwari 2 Desa Buddagan Kecamatan Pademawu Pamekasan - Nurul Ismaiyah (ABNA : Journal of Islamic Early Childhood Education, 2021)
The aims of this study is to determine the practice of prayer leraning in the habit of early childhood, behavior starting from the steps of learning takes place and also supporting factors and inhibiting factors in the process of learning the practice of prayer through habituation of early childhood behavior in PAUD Perwari 2 Buddagan Village Pademawu Pamekasan district. This research uses descriptive qualitative approach in the form of written words or narration. Data sources obtained through interviews, observations, and documentation. Then the data is analyzed with data analysis through data reduction, data display (data presentation) drawing conclusions. Then all data is checked for validity with an extended participation, persistence of observation and also triangulation. The result of this study indicate that first, the steps of learning the practice of prayer in the habit of early childhood behavior in PAUD Perwari 2 buddagan village pademawu sub-district namely, the steps of learning the practice of prayer begins with the introduction of prayer or intention before ablution, or it could be said to be preparation for the prayer. Then together carry out the pravtice of prayer with a slow reading and in accordance with the pillars of prayer. (a) supporting factors in the implementation of the practice of prayer one of which is the provision of rewards, completeness of facilities. (b) inhibiting factors namely, the location of worship centers that are narrow and less strategic and placement of prayer equipment that is not right so it looks less attractive. The benefits of learning the practice of this prayer children become aware of the procedures for the implementation of prayer correctly and in orderly manner based on the teachings of islam or can be said to be in accordance with the sharia through exercises that are carried out regularly and repeated so that it becomes a habit.